CFD analysis of pre-cooling water spray system in natural draft dry cooling towers. (25th July 2016) - Xia, Lin; Gurgenci, Hal; Liu, Deyou; Guan, Zhiqiang; Zhou, Ling; Wang, Pei
Highlights: Pre-cooling performance comparison between the HAN and the VAN is conducted. The VAN has superior performance than the HAN for the UQ NDDCT. Pre-cooling of 4.1–7.2 °C could be achieved under complete evaporation. The increasing of turbulence intensity could promote the pre-cooling performance. Abstract: CFD analysis of a wind tunnel with a single spray nozzle was conducted for the water spray system in the natural draft dry cooling tower (NDDCT) built at the University of Queensland. The CFD model was validated with the experiment results. The comparison of pre-cooling performance between the vertical arranged nozzle (VAN) and the horizontal arranged nozzle (HAN) shows that the VAN has better performance than the HAN within the inlet air velocity ( v a ) ranges (0.8–1 m/s) of the NDDCT during summer season. The impact of several physical parameters of the continuous phase on the maximum fully evaporated water mass flow ( m maxew ) with the VAN was also conducted. The results show that m maxew witnesses a decrease with the increasing of v a from 0.8 m/s to 1 m/s. The ambient air temperature and the relative humidity have significant impact on m maxew . The increasing of turbulence intensity could improve m maxew by enlarging spray coverage area.